Effect of sleep quality on the severity of perimenstrual symptoms in Japanese female students: a cross-sectional, online survey - Yukio Urabe; Makoto Komiya; Noriaki Maeda; Satoshi Arima; Tsubasa Tashiro; Rami Mizuta; Sakura Oda; Takaaki Nagasawa; Koichi Naito (BMJ Open)
Objectives To investigate the relationship between sleep quality and perimenstrual symptoms among Japanese female students.Design Observational, cross-sectional, online surveySetting We used an online questionnaire to collate responses from Japanese female students on sleep quality and perimenstrual symptoms.Participants A total of 298 female students aged 18–25 years in Japan were included in this study.Primary and secondary outcome measures The Menstrual Distress Questionnaire (MDQ) was used to assess the severity of perimenstrual symptoms for three periods—premenstrual, menstrual and postmenstrual—and the Japanese version of the Pittsburgh Sleep Quality Index was used to assess sleep quality. The MDQ scores were compared between two groups (normal-sleep quality and low-sleep quality) using Mann-Whitney U test. In addition, multiple logistic regression analysis was performed, and the MDQ subscales that showed significant differences between the groups were used as independent variables. The MDQ subscale that was strongly associated with sleep quality was calculated.Results Of the female students, 160 were classified into the normal-sleep quality group and 138 into the low-sleep quality group. The total MDQ scores were significantly higher in the low-sleep quality group at all phases of the menstrual cycle (respectively p<0.05). Among the MDQ subscales, ‘pain’ during menstruation and ‘concentration’ in the premenstrual and postmenstrual stages were associated with sleep quality (respectively p<0.05).Conclusions Improving sleep quality was one possible strategy to reduce the severity of perimenstrual symptoms. These results may provide useful information for Japanese female students who suffer from perimenstrual symptoms.